A retrospective investigation of the perceived influence of coaches, parents and peers on talented football players' motivation during development. Issue 6 (2nd November 2022) - McCann, Bryan; McCarthy, Paul J.; Cooper, Kay; Forbes-McKay, Katrina; Keegan, Richard J.
Abstract: This study retrospectively explored perceptions of coach, parent and peer motivational influences across athlete development. Four investment stage football players ( M age = 18.5 years, SD  = 0.6) with an average of 13 ( SD  = 1.4) years footballing experience, and four of their parents, were interviewed to investigate their perceptions of coach, parent and peer motivationally-relevant influence during the athletes' sampling, specializing and investment stages of development. Abductive thematic analysis of the interview transcripts identified five categories of perceived social agent motivationally-relevant influence that were consistent amongst each social agent and across each development stage. Each social agent was perceived by participants to play a role in each of the following motivationally-relevant categories of social agent influence: relationship factors; interpersonal interactions; support for development; support for participation; and feedback and evaluation. The categories were somewhat supportive and reflective of those outlined in other models. The results describe a complex and dynamic social environment within which players develop and provide insight into how this socio-motivational environment changes as athletes develop. Identified categories of perceived motivationally-relevant social agent influence may provide a framework for future research and allow practitioners to better determine athletes' motivational needs. Sport practitioners may use the findings from the study to ensure that athletes are gaining the breadth of motivational influences described in the categories within this study. Coach education might be developed or adapted to educate coaches on the types and importance of socio-motivational influences in sport.   Lay summary : Coaches, parents and peers were found to influence football players' motivation in a range of ways, including the quality of their relationship with athletes, their positive and negative behaviors, the support they provided players' development and participation in football, and the support they provided footballers to reflect on their experiences. The type of support that coaches, parents and peers provided to players changed as players progressed through different developmental stages, with coaches and peers becoming more important as athletes reached higher performance levels. Coaches and other sport practitioners might benefit from insight into the range of motivational influences that coaches, parents and peers can have in a football context in order to better develop and maintain athlete motivation.